Efektifitas Penurunan Kadar Lemak Pasien Obesitas Dengan Metode Jogging 30 Menit - Darul Husnul (Phsyical Education Health and Recreation Department of STKIP-YPUP Makassar, 2023)
The study aims to determine whether there is an effect of 30 minutes of jogging exercise on reducing fat levels. This type of research is a quasi-experimental design with one group pretest and posttest design. Sports program in the form of jogging for 30 minutes for 16 meetings. The population in this study were obese patients at the Tarowang Public Health Center with a total sample of 10 people. Jogging activities have a moving effect on all parts of the body so that the burning process in the body continues. This burning process is caused by an increased need for energy in the body because the energy balance changes drastically. With this activity (jogging) it causes the body to continue to need energy for a long time so that energy reserves continue to gradually decrease, this automatically makes the body need additional energy taken from fat and protein so that it automatically reduces fat reserves in the body. From this study, it can be concluded that there is an effect of the 30-minute jogging method on reducing fat levels in obese patients at UPT Tarowang Health Center. Statistically, a sig value of 0.00 (sig <0.05) was obtained, with a difference of 0.65 with the difference in BMI between the groups before jogging (pretest) and after jogging (posttest) = 0.94.